2002
DOI: 10.2337/diacare.25.10.1835
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic Neuropathic Foot Ulcers

Abstract: OBJECTIVE -The goal of this study was to evaluate whether simple risk factors can be identified that successfully characterize who will heal and who will not heal among patients who have received standard therapy for diabetic neuropathic foot ulcers.RESEARCH DESIGN AND METHODS -For this cohort study, we evaluated Ͼ31,000 individuals with a diabetic neuropathic foot ulcer seen in the Curative Health Services System. Using multivariate logistic regression, we evaluated the association between wound size, wound d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
178
4
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(200 citation statements)
references
References 23 publications
11
178
4
2
Order By: Relevance
“…Both Zimny et al (10) and Margolis et al (7)(8)(9) have noted a consistent relationship between ulcer area and the rate of healing, and we have confirmed this finding. Margolis et al (8) also noted a relationship between ulcer duration at first assessment and its cross-sectional area, as well as between both ulcer duration and area and the rate of subsequent healing, and we have also confirmed this observation.…”
Section: Results -supporting
confidence: 81%
See 1 more Smart Citation
“…Both Zimny et al (10) and Margolis et al (7)(8)(9) have noted a consistent relationship between ulcer area and the rate of healing, and we have confirmed this finding. Margolis et al (8) also noted a relationship between ulcer duration at first assessment and its cross-sectional area, as well as between both ulcer duration and area and the rate of subsequent healing, and we have also confirmed this observation.…”
Section: Results -supporting
confidence: 81%
“…However, a number of factors may underlie any residual differences in healing rate, including the general health of the patient, integrity of the arterial supply, and residual activity and weight bearing. Most importantly, Margolis et al (7)(8)(9) also observed that the rate of healing of neuropathic ulcers is affected by wound size, as well as by race and the duration of the ulcer at presentation. The influence of cross-sectional area has also been documented by Zimny et al (10).…”
mentioning
confidence: 99%
“…Thus, different presentations of foot ulcers can be encountered in clinical practice, and management strategies, outcome and resource utilisation are strongly influenced by characteristics of these, such as the presence of PAD, the presence of infection and, probably, the presence of comorbidity [1,7]. The number of large studies reporting on patient and ulcer characteristics is limited, but significant differences in the underlying pathologies and patient characteristics have been reported [1,[8][9][10]. These differences might be related to factors such as race and variation in demographics, but it is also likely that the characteristics of the local healthcare organisation will determine the type of patients that are reported on, owing to differences in referral.…”
Section: Introductionmentioning
confidence: 99%
“…Moves to reduce the incidence are likely to be most effective in those communities in which the baseline incidence is particularly high, and will be achieved mainly by improving access to effective primary care, with improved control of blood sugar and interventions to minimise the onset of complications such as peripheral arterial disease and neuropathy. Those with new diabetes-related ulceration of the foot should be referred promptly for expert assessment as an association has been demonstrated between time to expert referral and clinical outcome [3,4].…”
Section: Introductionmentioning
confidence: 99%